The Influence of Social Media Addiction on Academic Procrastination - Fathoni, Achmad Robbi (Journal of Mental Health and Social Rehabilitation, 2024)
Academic procrastination is a behavior exhibited by students involving the delay in starting or completing tasks for irrational reasons. This can negatively impact students' academic performance and mental health. Academic procrastination is caused by several factors, one of which is social media addiction. This study aims to determine the effect of social media addiction on academic procrastination. The participants in this study were 134 eighth-grade students from SMPN. Data collection in this study utilized a social media addiction scale. The results showed that social media addiction does not affect academic procrastination (p-values > 0.05).